Cortical Thickness Changes in Chronic Ketamine Users - Zhong, Jun; Wu, Huawang; Wu, Fengchun; He, Hongbo; Zhang, Zhaohua; Huang, Jiaxin; Cao, Penghui; Fan, Ni (Frontiers in Psychiatry, 2021)
Background: previous studies have examined the effects of long-term ketamine use on gray matter volume. But it is unclear whether the chronic ketamine use alters the cortical thickness，and whether the cortical thickness changes in chronic ketamine users are associated with cognitive deficits observed in chronic ketamine users. Methods: 28 chronic ketamine users and 30 healthy controls (HC) were recruited. Cortical morphometry based on Computational Anatomy Toolbox (CAT12) was used to measure cortical thickness. Cognitive performance was measured by MATRICS Consensus Cognitive Battery (MCCB). Two sample t-test was used to assess differences in cortical thickness and cognitive performance between the two groups. Partial correlation analysis was used for assessing correlations between cortical thickness changes and clinical characteristics, cognitive performance in chronic ketamine users. Results: chronic ketamine users exhibited signiﬁcantly reduced cortical thickness in frontal, parietal, temporal, and occipital lobes compared to HC (FDR-corrected at p < 0.05). In chronic ketamine users, the average quantity of ketamine use/day(g) was negatively correlated with cortical thickness in left superior frontal gyrus(SFG), right caudal middle frontal gyrus(MFG), and right paracentral lobule. The frequency of ketamine use(days per week) was negatively correlated with cortical thickness in left isthmus cingulate cortex. Duration of ketamine use(month) was negatively correlated with cortical thickness in left precentral gyrus. The chronic ketamine users showed signiﬁcantly poorer cognitive performance on the working memory (p= 0.009), visual learning (p= 0.009), speed of processing (p < 0.000), and Matrics composite (p= 0.01). There was no correlation between scores of domains of MCCB and reduced cortical thickness. Conclusion: The present study observed reduced cortical thickness in multiple brain areas, especially in PFC cortex in chronic ketamine users. Dose, frequency and duration of ketamine use was negatively correlated with cortical thickness of some brain areas. Our results suggest that chronic ketamine use may lead to decrease of cortical thickness. But the present study did not observe any correlation between reduced cortical thickness and decreased cognitive performance in chronic ketamine users. Keywords: ketamine, ketamine dependent, frontal lobes, gray matter, cortical thickness, surface-based morphometry